2017
DOI: 10.3389/fcimb.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with pCramoll Alone and in Combination with Fluconazole Provides Therapeutic Benefits in C. gattii Infected Mice

Abstract: Cryptococcus gattii is one of the main causative agents of cryptococcosis in immunocompetent individuals. Treatment of the infection is based on the use of antimycotics, however, the toxicity of these drugs and the increase of drug-resistant strains have driven the search for more effective and less toxic therapies for cryptococcosis. pCramoll are isolectins purified from seeds of Cratylia mollis, a native forage plant from Brazil, which has become a versatile tool for biomedical application. We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The treatment of C57BL/6 mice infected with C. gattii with the lectin from C. mollis seeds, alone or in combination with fluconazole, increased the survival and reduced morbidity as well as decreased pulmonary and cerebral fungal burden; the authors attributed the results to the immunomodulatory effect of the lectin (Jandú et al . ). In other work, a mannose‐binding lectin from Artocarpus heterophyllus promoted a Th1 immune response balanced by IL‐10 in experimental paracoccidioidomycosis in mice, leading to a reduction in the fungal burden in organs (Ruas et al .…”
Section: Use Of Lectins In the Treatment Of Micro‐organism Infectionsmentioning
confidence: 97%
“…The treatment of C57BL/6 mice infected with C. gattii with the lectin from C. mollis seeds, alone or in combination with fluconazole, increased the survival and reduced morbidity as well as decreased pulmonary and cerebral fungal burden; the authors attributed the results to the immunomodulatory effect of the lectin (Jandú et al . ). In other work, a mannose‐binding lectin from Artocarpus heterophyllus promoted a Th1 immune response balanced by IL‐10 in experimental paracoccidioidomycosis in mice, leading to a reduction in the fungal burden in organs (Ruas et al .…”
Section: Use Of Lectins In the Treatment Of Micro‐organism Infectionsmentioning
confidence: 97%
“…The combined treatment of pCramoll and fluconazole also significantly decrease the fungal load in the brain, reducing the morbidity and behavior changes caused by the infection (i.e., neuropsychiatric state, motor behavior, autonomic function, tone and muscle strength, and reflex/sensory function). Moreover, in vitro analysis revealed that bone marrow-derived macrophages treated with pCramoll were more able to phagocyte C. gattii , with higher production of reactive oxygen species, and decreased the intracellular fungal proliferation ( Jandú et al, 2017 ). These findings are summarized in Figure 2 .…”
Section: Plant Lectins For Treatment Of Fungal Infectionsmentioning
confidence: 99%
“…These paradoxical effects on the production of inflammatory mediators when comparing uninfected and infected hosts have been observed for other plant lectins 16,18,19 . For instance, the lectin isolated from Cratylia mollis (Cramoll) has been described as pro-inflammatory agent in in vitro and in vivo models 18,6163 ; however the treatment with this protein was shown to reduce the release of cytokines (such as TNF-α, IL-6) in experimental models of infection induced by S. aureus (using peritoneal cells) 18 and Cryptococcus gatti (using mice) 64 .…”
Section: Discussionmentioning
confidence: 99%